2014
DOI: 10.4161/trns.27526
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of in vitro transcription to the understanding of human RNA polymerase III transcription

Abstract: The discovery of constituents of eukaryotic transcription systems was enabled by the development of in vivo and in vitro methods for their study. Depending on the organism to be studied, the relative importance of each of these two general approaches has been different. Our knowledge about transcription of human genes would be considerably smaller without the results that were obtained by employing in vitro methods. Here, we will mainly focus on in vitro studies of gene expression that contributed to discoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 139 publications
(122 reference statements)
0
18
1
Order By: Relevance
“…However, contrary to what we observed in HEK293 cells, 7SL RNA levels were not decreased in mutant MO3.13 cells (Fig. S9), suggesting cell type–specific effects that could be related to upstream regulatory sequences specific to 7SL genes (31). In sum, we obtained two mutant cell lines with decreased levels of BC200 RNA (∼50% reduction in POLR3A M852V and absent in BC200 KO ), which was confirmed by Northern blotting (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, contrary to what we observed in HEK293 cells, 7SL RNA levels were not decreased in mutant MO3.13 cells (Fig. S9), suggesting cell type–specific effects that could be related to upstream regulatory sequences specific to 7SL genes (31). In sum, we obtained two mutant cell lines with decreased levels of BC200 RNA (∼50% reduction in POLR3A M852V and absent in BC200 KO ), which was confirmed by Northern blotting (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…5 a and Table S4). In contrast, vault RNA levels were comparable across both groups, making them the only transcripts with type 2 internal elements that were not decreased in mutants, which could be due to their vault RNA-specific distal regulatory sequences (31). Consistent with a selective effect on type 2 transcripts, none of the genes coding for type 1 (5S rRNA) or type 3 transcripts (U6 RNAs, Y RNAs, RPPH1, RMRP, and RN7SK) displayed significant differences between control and mutant samples, although some showed a small trend toward decreased expression in mutants (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The TATA Box or an AT-rich Sequence Is Sufficient to Recruit Human Polymerase II and III to Polymerase II Promoters-DNA sequence analysis of the Pol II promoters used in this study revealed the absence of typical Pol III promoter elements Box A/B/C, and PSE (4,45). It was notable, however, that the Pol II promoters from which Pol III initiated contained either a TATA box or an AT-rich sequence around bp Ϫ30 relative to the transcription start site.…”
Section: Multiple Polymerases Can Utilize Rna Pol II Promoters Inmentioning
confidence: 99%